The Interplay between Employee Development Factors and Succession Planning in Predicting Performance: A Case of Nepalese Commercial Banks - Yadav, Roshan (Nepalese Journal of Economics, 2025)
This study examines the interplay between employee development factors and succession planning in predicting performance of Nepalese commercial banks. Return on assets (ROA) and return on equity (ROE) are the dependable variables. The independent variables are succession planning, training and development, employee motivation, organizational culture and employee empathy. The study used primary and secondary sources of data. The primary source of data is used to assess the opinions of the respondents regarding the interplay between employee development factors and succession planning in predicting performance of Nepalese commercial banks. The study is based on primary data of 131 respondents. The secondary source of data is collected from 27 Nepalese commercial banks for the period from 2014/15 to 2020/21. The data are collected from Economic Survey published by Ministry of Finance, Quarterly Economic Bulletin published by Nepal Rastra Bank and annual report of NRB supervision and economic bulletin of World Bank. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and the interplay between employee development factors and succession planning in predicting performance of Nepalese commercial banks. The study showed that succession planning has a positive impact on return on assets and return on equity. It indicates that increase in succession planning leads to increase on return on assets and return on equity. Likewise, training and development has a positive impact on return on assets and return on equity. It indicates that increase in training and development facilities leads to increase on return on assets and return on equity. Similarly, employee motivation has a positive impact in performance. It means that fair employee motivation in the organization leads to increase on return on assets and return on equity. Moreover, organizational culture has a positive impact on return on assets and return on equity. It indicates that better the organizational culture, higher would be return on assets and return on equity. In addition, employee empathy has a positive impact in performance. It reveals that higher the employee empathy, higher would be the return on assets and return on equity.